1953
DOI: 10.1121/1.1906982
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Consonant Environment upon the Secondary Acoustical Characteristics of Vowels

Abstract: DESIGN OF HIGH FREQUENCY ANECHOIC TANKS 105 for use in the megacycle region can be simply constructed with a tan rho-c rubber liner. At a frequency of 3.35 megacycles a -}-inch thick liner provides results which are close to optimum, yielding a reflection coefficient of about--30 db up to an angle of incidence of about 60 ø . Above 60 ø the liner is highly ineffective. Theoretically, one would desire that the real part of the dilatational velocity in the rubber be slightly higher than that in water. In addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
269
0
11

Year Published

1983
1983
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 459 publications
(316 citation statements)
references
References 0 publications
20
269
0
11
Order By: Relevance
“…Port (1981) found that, in monosyllabic English words, vowels followed by voiceless consonants were 34% shorter than the same vowels followed by voiced consonants. Similarly, House and Fairbanks (1953) reported that vowels followed by voiceless consonants averaged 165 msec, while vowels followed by voiced consonants averaged 255 msec. In general, the dynamic range of vowel duration varies from 40 to 235 msec (Umeda, 1975).…”
Section: Methodsmentioning
confidence: 99%
“…Port (1981) found that, in monosyllabic English words, vowels followed by voiceless consonants were 34% shorter than the same vowels followed by voiced consonants. Similarly, House and Fairbanks (1953) reported that vowels followed by voiceless consonants averaged 165 msec, while vowels followed by voiced consonants averaged 255 msec. In general, the dynamic range of vowel duration varies from 40 to 235 msec (Umeda, 1975).…”
Section: Methodsmentioning
confidence: 99%
“…Thus it has been long known that different segments have different intrinsic durations which account for a lot of variation in segmental durations (Peterson and Lehiste, 1960;Klatt, 1976;van Santen, 1992): for example, high vowels tend to be shorter than low vowels. At the syllable level, in many languages vowels tend to be shorter when followed by a voiceless consonant than when followed by a voiced consonant (House and Fairbanks, 1953;Crystal and House, 1988) while consonants within a consonant cluster tend to be shorter than single consonants (Klatt, 1976).…”
Section: Sentence-level Timingmentioning
confidence: 99%
“…The relation between the phonological and the phonetic form is evaluated by cue constraints (CUE), and the phonetic form on its own is evaluated by articulatory constraints (*ART). As an example of a cue constraint, consider the fact that the duration of a vowel is a major cue to the voicing of a following obstruent in English, both in perception (Denes 1955, Raphael 1972) and in production (Heffner 1937, House & Fairbanks 1953, Luce & Charles-Luce 1985, but at most a weak cue in some other languages, both in perception (Morrison 2002, Broersma 2005 6 and in production (Keating 1979(Keating , 1985. Hence, the cue constraint *[long vowel duration] /obs,Avoice/ is ranked high in English but low elsewhere.…”
Section: Bidirectional Phoneticsmentioning
confidence: 99%